2010
DOI: 10.1155/2010/940528
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Quasi-Steady Characteristics for an Airfoil Oscillating at Low Reduced Frequencies

Abstract: Wind tunnel experiments were conducted on NACA-0015 airfoil model to investigate the effect of the reduced frequency (κ=0.0001to 0.5) and that Reynolds number (Re=0.2E06to 0.7E06) on the aerodynamic characteristics and hysteresis behavior associated with the oscillating motion of the airfoil. Pressure measurements were conducted on the midspan of the airfoil for quantitative results. Although dynamic stall study has been conducted to greater extent of reduced frequencies, for current work, emphasis is made on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Gupta and Ansell [9] and Geissler et al [20,22] also found such LEVs in the pressure distributions of the experimental data. Sharma and Poddar [27] found LEVs through the so-called Cn-Cm cross-correlation plots, which were obtained experimentally. In addition, Li et al [28] found LEVs in CFD and PIV results.…”
Section: Evolution Process Of Dynamic Stallmentioning
confidence: 84%
“…Gupta and Ansell [9] and Geissler et al [20,22] also found such LEVs in the pressure distributions of the experimental data. Sharma and Poddar [27] found LEVs through the so-called Cn-Cm cross-correlation plots, which were obtained experimentally. In addition, Li et al [28] found LEVs in CFD and PIV results.…”
Section: Evolution Process Of Dynamic Stallmentioning
confidence: 84%
“…Laminar separation bubbles (LSB) have been observed to be the incipient vortical structures at the leading edge of pitching NACA airfoils operating at low Reynolds numbers (Re = O(10 4 )-O(10 6 )), and the bursting of these bubbles has been related to the onset of dynamic stall [1,95,110,66]. The effect of an LSB on the surface pressure distribution has been well established, as there exists a well-defined plateau in the surface pressure distribution beneath the LSB.…”
Section: Vorticity Transport At Boundariesmentioning
confidence: 99%
“…(106) concluded for a variety of conditions, that the stall process, with laminar separation bubble, is initiated at the TE of the NACA0015 profile. Considering the TE CC capabilities of the CCNACA0018 airfoil, this is thought to be a favorable result as flow control authority increases as actuation is nearer the point of airfoil surface separation.…”
mentioning
confidence: 98%
“…numerous reports. Experiments bySharma, et al (92) (106) reported that Re effects increase at low pitch rates (approaching quasi-steady conditions), causing substantial rise in hysteresis behavior and stall AoA ( stall ) shift. As Re (0.7x10 6 ) increases, such hysteresis effects become negligible and Re effects become limited to the weakening in strength of DSV.…”
mentioning
confidence: 99%